2022
DOI: 10.1177/10711007221079617
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Antiglide Plating vs Lateral Neutralization Plating for Weber B Distal Fibular Fractures: A Systematic Review and Meta-analysis of Clinical and Biomechanical Studies

Abstract: Background: Distal fibular fractures are extremely common, yet there remains controversy about which type of plating technique is the most appropriate. We aimed to compare clinical and biomechanical outcomes following posterior antiglide plating and lateral neutralization plating for Weber B distal fibular fractures. Methods: A systematic review and meta-analysis of the literature was conducted by two independent reviewers according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Considering better soft tissue cover of implants, a posterolateral approach can be used for posterior malleolus fractures 25, , 21 as it allows simultaneous access to the fibular fracture, while antiglide plating of distal fibula appears to result in fewer hardware removal and reoperations than lateral plate positioning. 22,23 Bariteau et al 24 found that locking implants in lateral position provide greater stability in comminuted fractures. However, other authors take a critical view, 25,26 indicate higher costs and risk of wound complications.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…Considering better soft tissue cover of implants, a posterolateral approach can be used for posterior malleolus fractures 25, , 21 as it allows simultaneous access to the fibular fracture, while antiglide plating of distal fibula appears to result in fewer hardware removal and reoperations than lateral plate positioning. 22,23 Bariteau et al 24 found that locking implants in lateral position provide greater stability in comminuted fractures. However, other authors take a critical view, 25,26 indicate higher costs and risk of wound complications.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…The rates of peroneal tendon irritation, infection, and wound complications, operative time, and torque to failure did not differ. However, patients experienced greater odds of implant discomfort (OR, 2.96 [95% CI, 1.83 to 4.80]; p < 0.0001) and implant removal (OR, 2.48 [95% CI, 1.58 to 3.91]; p < 0.0001) after lateral plating compared with posterior plating 19 .…”
Section: Foot and Anklementioning
confidence: 99%
“…According to the applied position and biomechanical function, plates are used in a lateral neutralization mode or posterolateral antiglide mode. Biomechanical studies have shown that posterolateral antiglide plate fixation has more robust mechanical stability ( Schaffer and Manoli, 1987 ; Minihane et al, 2006 ; Buscharino et al, 2013 ; Deng et al, 2022 ). The posterolateral antiglide plate also has the advantages of less skin irritation, fewer wound complications, and a lower reoperation rate ( Winkler et al, 1990 ; Kilian et al, 2017 ; Wenger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%